Economic value added as a predictor of stock returns - Lak, Yau Huang (2008)
This research studies the effectiveness EVA as a predictor of superior stock returns and compares it against other indicators like P/E. The sample consists of 50 companies that are the largest in terms of market capitalisation as at June 1991. The period of the study is from 1991 to 1996. The 50 stocks are ranked according to EVA/Market Capitalisation (EVA/MktC). The annual returns of the top ten stocks in each year are then statistically tested against the annual returns of the bottom ten stocks. The overall results suggest that EVA is not an effective predictor of stocks with superior returns. Neither is it superior to P/E or P/B.